THE STUDY OF GRADUONYMY IN WORD GROUPS AND THE PRINCIPLES OF FORMING GRADUONYMIC SERIES - Mazmuna Rakhimovna Otaboyeva (Galaxy International Interdisciplinary Research Journal, 2023)
This article is devoted to study of history of the phenomenon of graduonymy. In this work is highlighted researches of Uzbek, Russian and English and German scientists and also given information about their investigations.